Positive electrode binder and preparation method thereof, preparation method of positive electrode plate and lithium battery
By using a fluorine-free positive electrode adhesive with a four-arm PEG structure, the problem of the prostate adhesive of lithium battery is easily deformed in an alkaline environment, and the effect of efficiently preventing slurry from condensing and improving battery performance is achieved.
Patent Information
- Application Number
- CN202510075946.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing lithium battery positive electrode binder is prone to elimination reactions and denaturation in an alkaline environment, affecting battery performance, and traditional improvement methods have problems such as environmental pollution and safety impacts.
A fluorine-free positive electrode adhesive including a four-arm PEG structure is used. The adhesive forms a mesh structure by adjusting the number and type of chain segments to enhance the bonding force with the positive electrode active material and avoiding the slurry coagulation.
It is achieved to effectively prevent the positive electrode slurry from condensing without adding harmful substances, improve the processing yield and performance of lithium batteries, and to avoid environmental pollution and safety influences.
Smart Images

Figure BDA0005247086610000021 
Figure BDA0005247086610000051 
Figure BDA0005247086610000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode binder and a preparation method thereof, a preparation method of a positive electrode sheet and a lithium battery. Background Art
[0002] With the development of science and technology, lithium batteries are widely used in various electronic devices, electric vehicles and other fields due to their high energy density, long cycle life and environmental protection. Among them, the preparation of the positive electrode of lithium batteries is one of the key factors affecting their performance. Lithium-ion positive electrode sheets include positive current collectors, positive active materials, binders, conductive agents, etc. At present, polyvinylidene fluoride (PVDF) is widely used as a binder for the positive electrode of lithium batteries due to its good chemical stability and electrochemical stability. However, in the lithium battery manufacturing system, the positive electrode active materials mainly include lithium iron phosphate or high nickel ternary, and most of the positive electrode active materials contain residual alkali to varying degrees. PVDF is prone to elimination reaction in an alkaline environment, resulting in denaturation, which not only makes the slurry gel difficult to process during production, but also affects the performance of the battery after being assembled into a lithium-ion battery.
[0003] To solve this problem, the method of adding inorganic acid or other organic solvents is usually adopted to adjust the pH value of PVDF slurry to prevent it from coagulation; or by changing the molecular structure of PVDF or adding other functional materials. However, these two methods of solving the problem still have other problems. First, adding inorganic acids or other organic solvents may pollute the environment and may affect the safety and stability of the battery. Secondly, the technical threshold for changing the molecular structure of PVDF or adding other functional materials is relatively high, the modification is difficult, and it may have a negative impact on the energy density and power density of the battery. Therefore, how to effectively prevent the coagulation of the positive electrode slurry and improve the performance of the battery without adding any harmful substances is an important challenge facing the current lithium battery manufacturing technology.
[0004] CN117038987A discloses a high-performance, low-cost positive electrode sheet and lithium-ion battery. The positive electrode sheet uses a polyacrylonitrile binder, and polyacrylonitrile is mixed with polyvinylidene fluoride for use. CN115763818A discloses a method for preparing a positive electrode slurry for a lithium battery using a fluorine-free binder. It introduces a polyacrylate copolymer and polyvinylidene fluoride as a positive electrode binder in a 1:1 mass ratio. Due to the characteristics of polyacrylate copolymers such as strong alkali resistance and fluorine-free and environmentally friendly, it can effectively improve the shortcomings of using polyvinylidene fluoride alone as a binder. CN117777899A discloses a preparation method and application of a highly alkali-resistant positive electrode binder for sodium batteries. The binder uses polyacrylic acid / acrylamide / styrene copolymer as the main component. The copolymer provides a large number of polar groups that can be well bonded to the positive electrode material and aluminum foil. As a fluorine-free binder, there is no gel phenomenon, and the peel strength of the electrode sheet is significantly improved.
[0005] However, since polyacrylate copolymers, polyacrylonitrile and polyacrylic acid / acrylamide / styrene copolymers are used as single binders, the resulting electrodes are relatively brittle and difficult to process, and PVDF cannot be completely abandoned. This results in the alkaline defluorination cross-linking reaction of PVDF still existing, making it impossible to achieve true anti-gelation.
[0006] Chinese patent CN117089017A discloses a non-fluorine binder for positive electrode of lithium ion battery, which is obtained by grafting alkyl glycidyl ether after copolymerization of acrylamide, acrylic acid and acrylonitrile. The hardness and brittleness of the used polymerization monomers (acrylamide, acrylic acid and acrylonitrile) are improved by introducing alkyl glycidyl ether, and the flexibility and dispersibility of the copolymer are improved. However, the carbon chain length and mass fraction of alkyl glycidyl ether are too high, which will lead to poor flexibility. In addition, the introduction of a large amount of alkyl glycidyl ether will reduce the bonding force. Summary of the invention
[0007] The object of the present invention is to provide a fluorine-free positive electrode binder with good flexibility and adhesion; another object of the present invention is to provide a method for preparing a fluorine-free positive electrode binder; another object of the present invention is to provide a method for preparing a positive electrode sheet that does not gel during homogenization and has good adhesion effect; another object of the present invention is to provide a lithium battery with excellent cycle performance.
[0008] A positive electrode binder, comprising a compound of formula (I):
[0009]
[0010] Wherein, a=1-500000, b=0-5000000, and R is an alkane, alkene or alkyne molecular chain containing one or more of carboxyl group, hydroxymethyl group, ether bond, ester bond, carbonyl group, cyano group, amide bond and benzene ring structure.
[0011] By adjusting the number and type of a and b segments, the flexibility and bonding strength of the adhesive can be changed to achieve the best bonding effect.
[0012] Furthermore, the weight average molecular weight of the compound is 1000-5000000 Da.
[0013] Furthermore, the compound has a four-arm PEG structure.
[0014] The four-arm structure gives the binder a highly branched property, which can form a network structure, enhance the binder's coating on the positive electrode active material, and improve the bonding force between the materials.
[0015] The present invention also discloses a method for preparing a positive electrode binder, comprising the following steps:
[0016] (1) In an atmosphere of protective gas, a solvent, a chain transfer agent, an emulsifier, and the first reactant, four-arm PEG acrylate, are mixed uniformly; the temperature is raised to 40-100° C.;
[0017] (2) adding the second reactant and the initiator and mixing them evenly; and performing copolymerization for 3-5 hours to obtain the compound.
[0018] The solvent is water; the chain transfer agent includes one of ethyl acetate, ammonium persulfate / sodium bisulfite, and dodecyl mercaptan; the emulsifier includes one of sodium lauryl sulfate and stearyl alcohol; and the initiator includes one of ammonium persulfate and azobisisobutyronitrile.
[0019] Furthermore, the second reactant includes one or a combination of at least two of octyl acrylate, acrylamide, acrylic acid, and acrylonitrile.
[0020] The polyethylene glycol and acrylate segments give the binder good flexibility, improve the brittleness of the positive electrode binder when used as a single binder, provide sufficient dispersibility, and can completely replace the PVDF binder without adding other functional components.
[0021] Furthermore, calculated by weight, the amount of the first reactant four-arm PEG acrylate added is greater than 0 parts and less than or equal to 20 parts; and the amount of the second reactant added is 80-100 parts.
[0022] The present invention also discloses a method for preparing a positive electrode sheet, comprising the following steps:
[0023] S1: uniformly mixing the positive electrode binder as described above with an organic solvent to obtain a glue solution;
[0024] S2: uniformly mixing the conductive agent and the glue to obtain a mixed solution;
[0025] S3: mixing the positive electrode active material and the mixed solution uniformly;
[0026] S4: uniformly mixing the positive electrode binder with the mixture obtained in step S3;
[0027] S5: Evenly mix the positive electrode active material with the material obtained in step S4 to obtain positive electrode slurry, apply the positive electrode slurry on the surface of the current collector, dry, and compact to obtain a positive electrode sheet.
[0028] Furthermore, the amount of the positive electrode active material added each time is half of the total amount.
[0029] The positive electrode sheet prepared by the present invention, in addition to the positive electrode binder, the conductive agent, the positive electrode active material and the addition of other additional components, will not affect the performance of the assembled lithium battery.
[0030] The organic solvent includes one of N-methylpyrrolidone, ethyl acetate, toluene, and xylene; the conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, and graphene; the positive electrode active material includes one or more of lithium iron phosphate, nickel cobalt manganese positive electrode material, nickel cobalt aluminum positive electrode material, cobalt-free positive electrode material, or lithium iron manganese phosphate.
[0031] Furthermore, in the step S5, the solid content and viscosity of the positive electrode slurry are adjusted by an organic solvent so that the solid content is 20-90% and the viscosity is 100-20000 mPa·s.
[0032] More preferably, the solid content is 60-75% and the viscosity is 7000-10000 mPa·s.
[0033] Furthermore, in the steps S1-S5, the ratio of the total mass of the added positive electrode binder to the mass of the conductive agent to the total mass of the positive electrode active material is 1-2:1:97-98.
[0034] The present invention also discloses a lithium battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte obtained by the preparation method described above.
[0035] The negative electrode sheet, separator and electrolyte are all commercial negative electrode sheets, separators and electrolytes in the prior art.
[0036] The present invention provides a positive electrode binder, which has no HF molecules being removed during use, can effectively prevent slurry from coagulating when PVDF is used as the positive electrode binder, improves the processing yield of the battery, avoids the pollution of fluorine-containing substances to the environment, and also avoids the influence of adding other components on the safety and stability of the lithium battery; the positive electrode binder has a large number of polar groups that can form a firm bond with the positive electrode active material and the current collector aluminum foil. DETAILED DESCRIPTION
[0037] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0038] Example 1
[0039] The preparation method of the positive electrode binder is as follows:
[0040] (1) 1600 ml of water was added to the reactor, and then vacuum was applied, nitrogen was introduced to form an atmosphere protection, 4 g of sodium dodecyl sulfate, 2 g of ethyl acetate, and 3 g of four-arm PEG acrylate (molecular weight ≈2000) were added, and then the temperature was raised to 60° C.
[0041] (2) Add 100 g of acrylic acid, 150 g of octyl acrylate, 30 g of acrylonitrile, and 25 g of 15 wt% ammonium persulfate to the reaction system of step (1), wherein the dropping rate of ammonium persulfate is 0.05 g / min, and the dropping rates of 100 g of acrylic acid, 150 g of octyl acrylate, and 30 g of acrylonitrile are all 0.3 g / min. The reaction is carried out for 5 hours to obtain a positive electrode binder (a is about 2000, b is about 10000-100000).
[0042] The preparation method of the positive electrode sheet is as follows:
[0043] The mass ratio of the positive electrode binder: the conductive agent: the positive electrode active material is 1.5:1:97.5. The positive electrode active material is LiNiCoMnO2 (NCM).
[0044] S1: 50 g of positive electrode binder was mixed with 1000 g of N-methylpyrrolidone (NMP) at a rotation speed of 1500-2000 rpm / min, and stirred and dispersed for 3 h to obtain a glue solution, and then vacuumed to remove bubbles.
[0045] S2: Add 50g of conductive agent carbon black into the glue solution, stir and disperse at a speed of 3000rpm / min for 1 hour to obtain a conductive glue;
[0046] S3: Add 2437.5 g of positive electrode active material into the conductive glue and stir for 1 hour at a speed of 3000 rpm / min. Stir for 1 hour.
[0047] S4: Add 25 g of positive electrode binder to the material obtained in step S3, rotate at 3000 rpm / min, and stir for 0.5 hours.
[0048] S5: Add the remaining 2437.5g of positive electrode active material, stir for 3 hours at a speed of 3000rpm / min, use NMP to adjust the solid content of the positive electrode slurry to 68%, and the viscosity to 8000mPa·s, apply the positive electrode slurry on the surface of the positive electrode collector aluminum foil at a speed of 5m / min, dry at 50-200℃, let stand at room temperature, cool, and roll until the compaction density reaches 3.5g / cc to obtain the positive electrode sheet.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the mass ratio of the positive electrode binder: the conductive agent: the positive electrode active material is 1:1:98.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that the mass ratio of the positive electrode binder: the conductive agent: the positive electrode active material is 2:1:97.5.
[0053] Example 4
[0054] The difference between this embodiment and embodiment 1 is that the mass ratio of the positive electrode binder: the conductive agent: the positive electrode active material is 2.5:1:97.5.
[0055] Example 5
[0056] The difference between this embodiment and embodiment 1 is that the positive electrode binder preparation method is:
[0057] (1) 1600 ml of water was added to the reactor, and then vacuum was applied, nitrogen was introduced to form an atmosphere protection, 4 g of sodium dodecyl sulfate, 2 g of ethyl acetate, and 3 g of four-arm PEG acrylate (molecular weight ≈4000) were added, and then the temperature was raised to 60° C.
[0058] (2) Add 100 g of acrylic acid, 90 g of octyl acrylate, 90 g of acrylonitrile, and 25 g of 15 wt% ammonium persulfate to the reaction system of step (1), wherein the dropping rate of the initiator ammonium persulfate is 0.05 g / min, and the dropping rates of 100 g of acrylic acid, 90 g of octyl acrylate, and 90 g of acrylonitrile are all 0.3 g / min. The reaction is carried out for 5 hours to obtain a positive electrode binder (a is about 4000, b is about 20000 to 200000).
[0059] Example 6
[0060] The difference between this embodiment and embodiment 1 is that the positive electrode active material is a lithium iron phosphate positive electrode material. The compaction density of the rolling in step S5 is 2.5 g / cc.
[0061] Comparative Example 01
[0062] The difference between this comparative example and Example 1 is that commercially available PVDF is used instead of the positive electrode binder provided by the present invention.
[0063] Comparative Example 02
[0064] The difference from Example 01 is that:
[0065] The difference between this comparative example and Example 1 is that a commercially available polyacrylate binder is used instead of the positive electrode binder provided by the present invention.
[0066] Performance Test:
[0067] The viscosity of the positive electrode slurry in step S5 of Example 1-6 and Comparative Example 1-2 was tested for 0-24h. The test results are shown in Table 1.
[0068] Table 1 Viscosity test results
[0069]
[0070]
[0071] It can be seen from Table 1 that Examples 1-6 will not gel rapidly within 0-24 hours, and the positive electrode binder has good anti-gelling property when the positive electrode is homogenized.
[0072] The positive electrode sheets prepared in Examples 1-6 and Comparative Examples 1-2 were assembled into soft-pack batteries with commercial negative electrode sheets, separators, and electrolytes. The positive electrode sheet peeling force was tested with a universal tensile machine; a constant current charge-discharge cycle experiment was performed with a charge-discharge current of 0.2C. The test results are shown in Table 1.
[0073] Table 2 Test results of positive electrode sheet peeling force, positive electrode sheet flexibility, and battery cycle capacity retention rate
[0074] project Pole peeling force N / m Flexibility 500 cycle capacity retention rate Embodiment 01 102 good 89 Embodiment 02 85 good 84 Embodiment 03 122 good 88 Embodiment 04 145 good 87 Embodiment 05 130 good 88 Embodiment 06 150 good 88 Comparative Example 01 75 generally 84 Comparative Example 02 49 Difference 81
[0075] It can be seen from Table 2 that the electrode flexibility and electrode peeling force of Examples 1-6 are higher than those of Comparative Examples 1-2, indicating that the positive electrode binder prepared in Examples 1-6 has excellent bonding performance, and the flexibility is better than that of PVDF and polyacrylate binders, and increasing the cyanide group and molecular weight will enhance the electrode peeling force.
[0076] Moreover, the cycle performance of the lithium battery of Examples 1-6 is better than that of Comparative Examples 1-2, and the 500-cycle capacity retention rate of Example 1 is the highest. The cycle performance of the lithium battery assembled with the positive electrode binder disclosed in the present invention is better than that of PVDF and polyacrylate binders. It should be noted that the amount of the positive electrode binder provided by the present invention is not easy to be too high or too low, and the amount of the positive electrode binder needs to be adjusted according to the system.
[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A positive electrode binder, characterized in that: Including compounds described by formula (I): Wherein, a=1-500000, b=0-5000000, and R is an alkane, alkene or alkyne molecular chain containing one or more of carboxyl group, hydroxymethyl group, ether bond, ester bond, carbonyl group, cyano group, amide bond and benzene ring structure.
2. A positive electrode binder according to claim 1, characterized in that: The weight average molecular weight of the compound is 1000-5000000 Da.
3. A positive electrode binder according to claim 1, characterized in that: The compound has a four-arm PEG structure.
4. A method for preparing a positive electrode binder, characterized in that: The following steps are involved: (1) In an atmosphere of protective gas, a solvent, a chain transfer agent, an emulsifier, and the first reactant, four-arm PEG acrylate, are mixed uniformly; the temperature is raised to 40-100° C.; (2) adding the second reactant and the initiator and mixing them evenly; and carrying out copolymerization reaction for 3-5 hours to obtain the positive electrode binder as claimed in any one of claims 1-3.
5. The method for preparing a positive electrode binder according to claim 4, characterized in that: The second reactant includes one or a combination of at least two of octyl acrylate, acrylamide, acrylic acid, and acrylonitrile.
6. The method for preparing a positive electrode binder according to claim 4, characterized in that: Calculated by weight, the addition amount of the first reactant four-arm PEG acrylate is greater than 0 parts and less than or equal to 20 parts; the addition amount of the second reactant is 80-100 parts.
7. A method for preparing a positive electrode sheet, characterized in that: The following steps are involved: S1: uniformly mixing the positive electrode binder according to any one of claims 1 to 3 with an organic solvent to obtain a glue solution; S2: uniformly mixing the conductive agent and the glue to obtain a mixed solution; S3: mixing the positive electrode active material and the mixed solution uniformly; S4: uniformly mixing the positive electrode binder with the mixture obtained in step S3; S5: Evenly mix the positive electrode active material with the material obtained in step S4 to obtain positive electrode slurry, apply the positive electrode slurry on the surface of the current collector, dry, and compact to obtain a positive electrode sheet.
8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: In the step S5, the solid content and viscosity of the positive electrode slurry are adjusted by an organic solvent so that the solid content is 20-90wt% and the viscosity is 100-20000mPa·s.
9. The method for preparing a positive electrode sheet according to claim 7, characterized in that: In the steps S1-S5, the ratio of the total mass of the added positive electrode binder to the mass of the conductive agent to the total mass of the positive electrode active material is 1-2:1:97-98.
10. A lithium battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte obtained by the method for preparing a positive electrode sheet according to any one of claims 7 to 9.
Citation Information
Patent Citations
Method for preparing lithium battery positive electrode slurry by using fluoride-free binder
CN115763818A
High-performance low-cost positive plate and lithium ion battery
CN117038987A
Lithium ion battery positive electrode non-fluorine binder, and positive electrode and battery using lithium ion battery positive electrode non-fluorine binder
CN117089017A
Preparation method and application of high-alkali-resistance positive electrode binder for sodium battery
CN117777899A
Biologically related substances modified by multifunctional H-type polyethylene glycol derivative
CN104530413A